2017
DOI: 10.1017/s1352465817000285
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Acceptance and Commitment Therapy Delivered by Psychologists and Non-Psychologists in an NHS Community Adult Mental Health Service: a Preliminary Analysis

Abstract: Background: Previous studies have demonstrated Acceptance and Commitment Therapy (ACT) is effective for depression and may be useful for complex transdiagnostic clients. Aims:To conduct a preliminary evaluation whether ACT is feasible and effective when delivered by psychologists and non-psychologists for complex clients in a National Health Service (NHS) community mental health service for adults.Method: Staff were trained in ACT and conducted one-to-one therapy with clients. Measures on general mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The quality of treatment and adherence to the treatment model could have been improved through visual-or audio recordings and the possibility of random audit of sessions by an outside expert. Overall, the present studies indicate that good outcomes can be attained with adequately supervised staff, students or novice therapists (Ekers et al, 2011;, even when they lack a mental health background (Richardson et al, 2017), and that in some cases outcomes can be comparable with those of professionals (Goldstein, 2015).…”
Section: Limitationsmentioning
confidence: 60%
See 3 more Smart Citations
“…The quality of treatment and adherence to the treatment model could have been improved through visual-or audio recordings and the possibility of random audit of sessions by an outside expert. Overall, the present studies indicate that good outcomes can be attained with adequately supervised staff, students or novice therapists (Ekers et al, 2011;, even when they lack a mental health background (Richardson et al, 2017), and that in some cases outcomes can be comparable with those of professionals (Goldstein, 2015).…”
Section: Limitationsmentioning
confidence: 60%
“…Either a psychologist-or non-psychologist -delivered ACT intervention for depression was examined in a community mental health services program (Richardson et al, 2017). The results tentatively indicated that overall ACT may be effective in clients with complex co-morbidities including depressive symptoms.…”
Section: Face-to-face Acceptance-and Value-based Interventions For Dementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Sairanen et al (2018) found that increased mindfulness skills and decreased cognitive fusion were associated with lower distress, suggesting that therapies targeted at increasing mindfulness and cognitive defusion, such as Acceptance and Commitment Therapy (ACT), are likely to be effective at reducing parental distress. ACT can be effectively delivered in the clinic by non-psychologists (T. Richardson, Bell, Bolderston, & Clarke, 2018), which suggests that it could be trialled in the clinic by appropriately trained and skilled audiologists as a tool for managing parental distress.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%